Anatomical and physiological aspects of cucumber graft - Baron, Daniel; Saraivo, Gustavo Francisco Rosalin; Amador, Talita Silveira [UNESP]; Rodrigues, João Domingos [UNESP]; Goto, Rumy [UNESP]; Ono, Elizabeth Orika [UNESP] (Lepidus Tecnologia, 2018)
The grafting of two cucumber scions [Cucumis sativus L.]—Taiko hybrid and Tsuyoi hybrid— onto a Tropical hybrid pumpkin rootstock (Cucurbita moschato L.) was studied. The study was conducted in a greenhouse. Plants grafted using the tongue approach grafting technique were compared with ungrafted plants. We evaluated the initial establishment of grafting through anatomical cuts on the region of union graft and examining leaves chlorophyll index (SPAD) and their levels of chlorophyll a, chlorophyll b and total chlorophyll. The experimental design utilized randomized blocks and the data were subjected to variance analysis (ANOVA) and the Tukey Test at 5% probobility. The results indicate that Taiko cucumber scions are best grafted onto Tropical pumpkin rootstock, since these exhibits early grafting establishment. Moreover, when compared to grafting using Tsuyoi cucumber scions, Taiko cucumber scions present higher SPAD index values and levels of chlorophyll a and total chlorophyll.
Keywords: Chlorophyll; Cucurbitaceae; Plant onotomy; Plont propagation